(untitled) (International Journal of Engineering and Computer Science, 2015)
The single carrier multiple access scheme is a novel method of radio transmission currently used in long term evolution (LTE) technology for uplink due to its high data rates and lower peak-to-average power-ratio (PAPR) as compared to OFDM technique. In this paper we analytically derive the time domain SC-FDMA signal and numerically compare the PAPR characteristics using the complementary cumulative distribution function (CCDF) of PAPR with the help of raised cosine (RC) and root raised cosine pulse (RR) shaping method and discuss the resulting PAPR of both the mapping schemes. Comparing the two forms of SC-FDMA, we find that interleaved (FDMA) has lower PAPR than localised (FDMA). We also discuss the SNR (signal to noise ratio) performance of both LFDMA and IFDMA schemes and find that the SNR performance of localised (FDMA) is better than interleaved (FDMA) technique.